Sigurd Wettenhovi-Aspa, August Strindberg and a dispute concerning the common origins of the languages of mankind 1911–1912 - Pitkälä Pekka (The Donner Institute for Research in Religious and Cultural History, 2022)
This article is about the notions of history and language of a Finnish artist and writer Sigurd Wettenhovi-Aspa (née Sigurd Asp, 1870–1946), and the Swedish writer August Strindberg (1849–1912), and their interaction. Wettenhovi-Aspa and Strindberg knew each other from Paris, where both lived in the 1890s. In the 1910s they both published books and articles on their respective linguistic views. According to both of them, the languages of mankind had a common origin. Strindberg had a more traditional view, as according to him Hebrew was the original language of the world. For Wettenhovi-Aspa, the original language was Finnish. These ideas may seem eccentric, but I argue that they both reflect the intellectual currents of their own time and are connected with a long tradition as well.